Poverty and choice of healthcare services among women in Calabar Metropolis, Cross River State, Nigeria (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examines the impact of poverty on the healthcare service choices of women in Calabar Metropolis, Cross River State, Nigeria. Poverty remains a significant barrier to accessing healthcare services, particularly for women, as it affects their ability to afford necessary medical treatments. The study explores how factors such as educational level, income, and affordability influence healthcare choices among women. A descriptive research design was adopted, utilizing a sample of 400 women from Calabar Metropolis. The findings reveal that lower educational levels and limited income are strongly correlated with the preference for public healthcare services and traditional remedies.Additionally, high costs in private healthcare facilities discourage many women from seeking proper medical attention. This study highlights the need for targeted interventions that address both financial and educational barriers to improve healthcare access for women in poverty-stricken areas.
Keywords: Poverty; Healthcare services; Women; Educational level; Income; Affordability